A new fluorescent macrocyclic nano-chemosensor for Fe3+ and I− in aqueous solution. (10th October 2018) - Azadbakht, Reza; Chehri, Neda
Abstract : A fluorescent nano-chemosensor, capable of detecting Fe 3+ and I − in aqueous media, has been designed and synthesized. Abstract : A new Schiff base fluorescent chemosensor (L1) and its reduced form (L2) have been designed and synthesized. Nanoparticles of L2 were also prepared by using a nanoprecipitation method. The nano-chemosensor of L2 shows very high selectivity and sensitivity towards Fe 3+ and I − ions in aqueous buffer solution. L2 also shows selective detection and discrimination of Fe 3+ and Fe 2+ in an aqueous environment. The lowest detectable concentration of Fe 3+ ions by L2 was found to be 68 nM.